PROBLEMATIC ASPECTS OF RISK MANAGEMENT OF INVESTMENT AND INFRASTRUCTURE PROJECTS FOR THE REСONSTRACTION OF UKRAINE - Kropelnytska , S.O.; Kryhovetska , Z.M.; Matskiv , V.V.; Plets , I.I. (The actual problems of regional economy development, 2023)
The scientific research presented in the article is focused on the consideration and substantiation of the main and current problematic aspects of the use of risk management tools and recommendations for their optimal combination to ensure the maximum risk management efficiency in the implementation of investment and infrastructure projects for the reconstruction of Ukraine. The article uses the methods of theoretical analysis of scientific literature, statistical analysis to study and systematize data on the volume of economic losses during the full-scale war in Ukraine and to assess the needs for recovery investments by economic sectors, and to make a comparative analysis of insurance and guarantee instruments for risk management of investment and infrastructure projects, taking into account the military and political conditions of their implementation, etc. The results of the study show that investment and infrastructure projects can be managed with the use of insurance and guarantee instruments in a way that is more effective than other methods of risk management. The results of the study showed that investment and infrastructure projects for the reconstruction of Ukraine are accompanied by significant risks related to the uncertainty of economic and political conditions during Russia's war against Ukraine, financial and technical procedural problems, changes in legislation, in particular regarding investment incentives, etc. In order to effectively manage these risks, it is necessary to use a comprehensive approach, including the development of a risk management strategy, the definition of risk control and monitoring procedures, the use of financial, guarantee, insurance and digital tools, etc. The scientific novelty of the study is to raise the issue of the need to develop an optimal combination of risk management tools for investment and infrastructure projects for the reconstruction of Ukraine in the face of the uncertainties associated with the war and post-war period and its conditions. The practical significance of the study is that the results of the study can be used by managers, investors and developers of projects for the reconstruction of the Ukrainian economy both in the current state of martial law and after its termination.